Violation of children `s rights by Varemba cultural practise in Mberengwa District 1980-2013 - Bulabula, Nokuthula (Midlands State University, 2014)
The study sought to unpack the cultural practises and social way of life of the Varemba in Mberengwa. The Varemba ethnic group in Mberengwa practise is a distinctive group which practise cultural practise such as Komba initiation school for girls and Murundu known as male circumcision for boys, virginity testing, Female genital Mutilation (fgm),son preference, inheritance. In this group all boys and girls should undergo traditional initiation school to graduate into manhood and womanhood respectively. It will be demonstrated that children in the Varemba have been seriously affected by cultural practises which result in devastating effects such as health problems and also hinder development capacity of the district since many children do not proceed to secondary school. It will be demonstrated that cultural practises have devastating effect on the well being of a child and child development. The government also introduced the Victim Friendly Unit under ZRP to deal with child abuse cases and BEAM to cater for school fees for the poor and girls who will be sacrificed to get married so that the boy will go to school. The study will also highlight the efforts by the NGOs to curtail violation of child rights through cultural practises and also address the issue of gender inequality. It will also unravel the effectiveness of all these foundations and the role of the community, religious leaders in supporting the laws that are passed to protect children from harmful cultural practise.